21.1k views
0 votes
Given the two points (-1, 6) and (3, -2), write an equation in point-slope form.

2 Answers

4 votes

Answer:

y - 6 = -2(x + 1)

Explanation:

Slope: (-2-6)/(3--1)

= -8/4

= -2

y - 6 = -2(x - -1)

y - 6 = -2(x + 1)

User Christian Severin
by
4.8k points
1 vote

Answer:

y-6 = -2(x+1)

Explanation:

First we need to find the slope

m = (y2-y1)/(x2-x1)

= (-2-6)/(3--1)

= (-2-6)/(3+1)

= -8/4

= -2

Then we can point slope form where

y -y1 = m(x-x1)

where m is the slope and x1,y1 is a point

y-6 = -2(x--1)

y-6 = -2(x+1)

User Blitzkriegz
by
4.4k points